Pertumbuhan Vegetatif dan Generatif Batang Atas Jeruk Pamelo ‘Nambangan’ pada Empat Jenis Interstok - Slamet Susanto; Herik Sugeru; Sri Minten (Jurnal Hortikultura Indonesia, 2010)
ABSTRACTThe objective of this research was to study the differences effects of interstock on scion growth, flowering and fruiting of ‘Nambangan’ pummelo (Citrus grandis (L.) Osbeck). The research was conducted from January to December 2005 in a green house of Cikabayan Research Station IPB, Dramaga. Th e research was arranged in randomized completely block design with singe factor i. e. kind of intertock consisted of Flying Dragon, Troyer, Citrumelo, and Rangpur Lime. All interstocks were grafted on Javanche Citroen rootstock. The result showed that the growth, flowering and fruiting of ‘Nambangan’ pummelo was significantly affected by kind of interstock. Citrumelo interstock tended to induce more vegetatif with low generatif growth of ‘Nambangan’ scion. Troyer, Rangpur Lime and Flying Dragon resulted in moderate growth of ‘Nambangan’ scion, however only Flying Dragon induced ‘Nambangan’ scion to produce more flower and fruit as compared with other interstocks. There was no significant different in carbohydrate content in leaves and C/N ratio among scion with four interstock studied.Key words: interstock, Nambangan, pummel o, flowering